Growth Curve of Crioulo Foals from Birth until 24 Months of Age - Moraes, Bruna dos Santos Suñé; Amaral, Lorena Alvariza; Finger, Ilusca Sampaio; Mazzini, Ana Rita Assumpção; Pazinato, Fernanda Maria; Curcio, Bruna da Rosa; Nogueira, Carlos Eduardo Wayne (Acta Scientiae Veterinariae, 2017)
Background: Breeding of Crioulo horses in the southern region of Brazil is very significant. Notwithstanding, not all animals meet the standards defined for the breed, raising concern among breeders, owners and veterinarians, driving them to an effort to know and understand the development of Crioulo foals. In order to get a registry at Brazilian Association of Crioulo Horse Breeders (ABCCC), the foals must be presented to a certified technician as of 24 months of age and show the breed standards and measurements required. To date, there are no data concerning development of this breed available. Therefore, this study aims to describe the growth curve of Crioulo foals in the south region of Rio Grande do Sul. Materials, Methods & Results: The study was conducted in three Crioulo horse breeding farms in the cities of Santa Vitória do Palmar, Bagé and Aceguá, in the state of Rio Grande do Sul, Brazil, for a period of two years (2013-2015). We followed up on 267 Crioulo foals from birth up to 24 months of age. Biometric evaluation was divided in 26 periods, with 40 animals in each and random repetition of individuals. Period one: birth to seven days; period two: seven to 21 days; monthly from 1st to 24th month. The three breeding farms presented similar environmental conditions and the horses were submitted to similar management. Measurements were taken on a monthly basis, using a mechanical scale for weight and a hippometer for height. The analysis were conducted on SAS/ETS® version 9.2. Logistic non-linear regression model was used to obtain growth curves for height and minimum, medium and maximum weight of the foals on their respective ages, by this way six growth curves were produced. Results show an increase in weight and height at 24 months of age compared to the moment of birth. This increase was accentuated during the first months of life, both in weight and height. Thus, it is possible to observe that the first six months of life is characterized by a larger growth rate and is therefore, essential for the foals development, requiring special attention from the breeder and owner. Discussion: The growth curve obtained show that not all individuals reach the measurements required by the breed’s association, corroborating the empirical observation of breeders and technicians in their routine. This is also a concern related to other Brazilian breeds such as Mangalarga Marchador, Pantaneira, Campeira. For the mentioned breeds, the adequate growth curve has already been described aiming to controlling foal development. The ABCCC require that foals as of 24 months of age have the minimum values of 1.40 m 1.38 m and 1.38 m; and maximum values of 1.50 m, 1.48 m and 1.50 m, for males, females and geldings, respectively, in order to receive the Association brand and the permanent registry. According to the growth curve, the first two months of the foal’s life show the largest growth rate, reaching 78.4% of an adult’s height with average growth of 20 cm, reaching 1.05 m. Genetic features, nutritional and sanitary conditions, directly influence this period. Overweight associated to exercising increases the risk of musculoskeletal injury and represent a factor for stress on the joints. This should be a concern among Crioulo breeders and the knowledge of their growth curve is important for an objective assessment seeking for a gradual and weighted development. In this work, it was possible to determine the growth curve of Crioulo breed foals in the south region of Rio Grande do Sul, from birth up to 24 months of age, providing minimum, medium and maximum parameters referring to withers height and body weight.